Reevaluating Price Value: Exploring Emotional and Social Motivations in K-pop Fans' Social Media Use - Roslan, Muhammad Amirul Asyraaf (Advances in Humanities and Contemporary Studies, 2024)
This study investigates the role of Price Value (PV) within the Unified Theory of Acceptance and Use of Technology (UTAUT) framework, focusing on social media (SM) usage among K-pop fans. K-pop fandom is characterised by its intense engagement with SM platforms for content consumption, interaction with idols, and community participation. However, little is known about how perceived costs—such as time, data usage, or paid features—affect fan behaviour, particularly in relation to PV as conceptualised in UTAUT2. This study addresses a critical gap by examining whether PV influences K-pop fans' BI to use SM platforms, which are largely free or low-cost. Using qualitative methods, the research employs focus group discussions (FGDs) to explore how K-pop fans perceive and evaluate the costs associated with SM. A total of 15 participants were involved in this study to contribute their insights. Findings suggest that emotional and social rewards, such as interactions with idols and fan communities, far outweigh concerns about direct or indirect costs. PV is found to be less significant, as fans' engagement is driven more by emotional and social benefits than by monetary considerations. This research contributes to the UTAUT2 model by highlighting the limited role of PV in contexts where emotional and social rewards dominate. The findings also provide practical implications for platform developers and marketers, suggesting that enhancing emotional and social engagement strategies may be more effective than focusing on cost-related factors.